2012
DOI: 10.1111/j.1365-2702.2011.04006.x
|View full text |Cite
|
Sign up to set email alerts
|

Support groups for caregivers of intellectually disabled family members: effects on physical–psychological health and social support

Abstract: The support group is an effective alternative intervention for promoting caregivers' physical-psychological health status as well as their social support. Therefore, the support group should become a routine component of the caregiver of people with intellectual disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
0
18
0
4
Order By: Relevance
“…A social support group can be used as an intervention for informal caregiver burden. In a study investigating the effectiveness of a support group for caregivers (N = 72) of family members with intellectual disabilities, results indicated that symptoms of depression and anxiety decreased while positive social interactions increased after the intervention (Wei et al, 2012). Similarly, in review of 30 quantitative and quasi-experimental controlled trialed studies on the effectiveness of support groups for caregivers of patients suffering from dementia, results from the meta-analysis indicated that support groups are beneficial for caregivers (Chien et al, 2011).…”
Section: Social Supportmentioning
confidence: 94%
“…A social support group can be used as an intervention for informal caregiver burden. In a study investigating the effectiveness of a support group for caregivers (N = 72) of family members with intellectual disabilities, results indicated that symptoms of depression and anxiety decreased while positive social interactions increased after the intervention (Wei et al, 2012). Similarly, in review of 30 quantitative and quasi-experimental controlled trialed studies on the effectiveness of support groups for caregivers of patients suffering from dementia, results from the meta-analysis indicated that support groups are beneficial for caregivers (Chien et al, 2011).…”
Section: Social Supportmentioning
confidence: 94%
“…themes relating to a new perspective and self-compassion) (Hayes, Strasahl, & Wilson, 1999;Smith & Gore, 2012) and participants often described their experience using metaphors from the workshops. This suggests that the effectiveness of the intervention was due to more than social support alone, though this in and of itself was also highlighted as an important factor and is highlighted by previous research as important for family carer wellbeing and health (Dunst, Trivette, & Cross, 1986;Guralnick, Hammond, Veille, & Connor, 2008;Skok, Harvey, & Reddihough, 2006;Wei et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Ownsworth et al [ 19 ] assessed cancer caregivers for factors that may moderate caregiver psychological well-being and found that psychological well-being was associated with satisfaction in social support and resources. In a study with caregivers of individuals with intellectual disabilities, results indicated that symptoms of depression and anxiety decreased while positive social interactions increased after the intervention [ 20 ]. Similarly, results from a review of 30 quantitative and quasi-experimental controlled trialed studies on the effectiveness of support groups for caregivers of patients suffering from dementia indicated that support groups are benef icial for caregivers [ 21 ].…”
Section: Caregiver Concernsmentioning
confidence: 96%